Assessing Students’ Learning in MIS using Concept Mapping - Gregoriades, Andreas; Pampaka, Maria; Michail, Harris (My University, 2009)
The work described here draws on the emerging need to internationalize the curriculum in higher education. The focus of the study is on the evaluation of a Management Information Systems (MIS) Module, and the specification of appropriate course of action that would support its internationalization. To realize this goal it is essential to identify the possible learning needs of the two dominant cultural groups that compose the university student population in Britain, specifically European and Asian (UUK, 2005). Identification of knowledge patterns among these cultural groups is achieved through the application of a concept mapping technique. The main research questions addressed are: (1) How to internationalize the MIS module’s content and teaching methods to provide for students from different cultural backgrounds? (2) What are the main gaps in knowledge of students in MIS? The paper presents the results of this study and proposes actions needed to streamline the current teaching methods towards improving the quality of the students’ learning experience.
Keywords: MIS Internationalization; Concept Mapping; Learning Assessment; Knowledge Gaps